Functional MRS studies of GABA and glutamate/Glx – A systematic review and meta-analysis. (January 2023) - Pasanta, Duanghathai; He, Jason L.; Ford, Talitha; Oeltzschner, Georg; Lythgoe, David J.; Puts, Nicolaas A.
Abstract: Functional magnetic resonance spectroscopy (fMRS) can be used to investigate neurometabolic responses to external stimuli in-vivo, but findings are inconsistent. We performed a systematic review and meta-analysis on fMRS studies of the primary neurotransmitters Glutamate (Glu), Glx (Glutamate + Glutamine), and GABA. Data were extracted, grouped by metabolite, stimulus domain, and brain region, and analysed by determining standardized effect sizes. The quality of individual studies was rated. When results were analysed by metabolite type small to moderate effect sizes of 0.29–0.47 (p < 0.05) were observed for changes in Glu and Glx regardless of stimulus domain and brain region, but no significant effects were observed for GABA. Further analysis suggests that Glu, Glx and GABA responses differ by stimulus domain or task and vary depending on the time course of stimulation and data acquisition. Here, we establish effect sizes and directionality of GABA, Glu and Glx response in fMRS. This work highlights the importance of standardised reporting and minimal best practice for fMRS research. Highlights: A comprehensive systematic review and meta-analysis of functional MRS studies of GABA, Glx, and Glutamate. Sophisticated approach to studying the effect of approach, stimulus, region, and data quality. We show large heterogeneity and small effect sizes, and highlights the importance of standardised reporting and minimal best practice.